Política criminal como limite à expansão do direito penal de perigo abstrato - Torres, Rafael Lima (2021)
The present research in search of the situation of the role of the criminal policy within the penal system, from the legislative production to the application of the penalty, going through the entire process of judicial interpretation and concretization of the law. The relationship between criminal policy, criminology and its main schools, as well as the way in which social control is carried out for a political-criminal containment of the population are highlighted. The study also analyzes some criminal policy models that do not take human rights into account, and the risks of this type of repressive and unconstitutional measure with regard to aggression against human dignity. Still, it aimed to verify the relationship between humanist criminal policy, dogmatic application and concepts of legal good, to study the importance of these elements for Criminal Law and to define criteria for the analysis of types of penalties provided and crimes of abstract danger by the magistrate